Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Best answer

When x=3, so 2-x applies and 2-x=2-3=-1 so f(3)=-1.

When x=0, so x+1 applies and f(0)=x+1=1.

by Top Rated User (610k points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,167 questions
86,658 answers
2,246 comments
76,258 users